Impact of Processing on Retention of Beta Carotene of Sweet Potatoes - Rayamajhi, Ujjal; Mishra, Achyut (Journal of Food Science and Technology Nepal, 2020)
The study was carried out to evaluate the impact of processing on retention of beta-carotene of sweet potatoes. Eight cultivars of sweet potatoes were used in the study; among which four cultivars were of orange-fleshed varieties viz. ‘CIP 440012’, ‘CIP 440015’, ‘CIP 440267’ & ‘CIP 440021’, and four cultivars were of white fleshed varieties viz. Lamatar White, Balewa Red, Sangachowk Red and Barbote White. The proximate composition and micronutrient composition of eight cultivars of raw sweet potatoes were determined. The carotene content of sweet potato cultivars was also calculated. Finally, the retention of carotene content in sweet potato cultivates under various processing methods (viz. boiling for 30 minutes at 100°C, baking in a microwave oven at 200°C for 30 minutes and drying in a cabinet dryer for 12 hours at 60°C) was observed. The orange fleshed varieties (CIP cultivars) had the greater proximate composition than the white fleshed varieties (local cultivars). The micronutrient composition of orange fleshed sweet potatoes and white fleshed varieties were similar. But the carotene content of the orange fleshed varieties was greater; ranging from 14.43-22.11 mg/100gm. The white fleshed varieties had a low carotene concentration of 0.70-1.83 mg/100gm. The retention of carotene content was observed higher in the boiling process (79%-89%) followed by baking (56%-78%) and least in drying (44%-67%). Also, the orange fleshed varieties had a better retention capability than white fleshed varieties in all the processing methods. Thus, orange fleshed sweet potatoes had a better nutrient profile with higher retention capabilities.